An integrative description of Ramazzottius subanomalus (Biserov, 1985 (Tardigrada) from Poland - Stec, Daniel; Zawierucha, Krzysztof; Michalczyk, Łukasz (Zootaxa, 2017)
A population of Ramazzottius subanomalus (Biserov, 1985) was found in a moss sample collected from concrete wall in Poznań, western Poland. Animals were prepared for light and scanning electron microscopy and for DNA sequencing to provide an integrative description of the species that was originally described only by means of classical alpha taxonomy. As a result of our studies, we provide the first ever SEM photomicrographs of Ramazzottius subanomalus individuals and their buccal apparatuses. Additionally, we present new DNA sequences as well as new morphometric data for R. subanomalus. The molecular data comprise sequences for three DNA fragments, one mitochondrial (COI) and two nuclear (18S rRNA and 28S rRNA). As a result of being able to analyse a considerable number of animals and eggs, our study has expanded some of R. subanomalus morphometric traits ranges; compared with those provided in the original description. The spine-shaped egg processes as well as qualitative and quantitative characters of adults show R. subanomalus is most similar to Ramazzottius anomalus (Ramazzotti, 1962). However, our study has shown that R. subanomalus differs from R. anomalus by the lack of fine granulation on eggshell surface as well as by three other morphometric characters: longer buccal tube and two aspects of the placoids. We also discuss the validity of the R. anomalus record in Poland in the light of our findings. Finally, we show that the extreme eggshell variability in this species is observed both in natural and laboratory environments.